(untitled) (ModaPalavra e-periódico, 2017)
Aiming to discuss about social division of labour and how it appears in the fashion design field, in addition to debate about the social role of fashion designer in the production chain, this paper presents two opposing notions that aim to explain important changes that have occurred inindustrial society in the second half of twentieth century: “post-industrial society” of the author Daniel Bell, and “late capitalism” from Ernst Mandel. Each of these theories come from different ideological positions and impacts on the field of design with regard to theoretical production and the professional qualification and practices of designers. Thus, through bibliographic research, we began this paper with a reflection on the materiality and immateriality production in design. Then we confront these two important theoretical currents and relate them to others that we believe to be arising from one of them –"end of work", "design as a process" –and to objective and concrete issues of one of the design branches in which material production and the huge number of workers are undeniable: the fashion design field. Among these issues are the social division of labour and the propagation of the mythical notion of the individual creator, even propagated by the education system.